REAKSI SAHAM MANUFAKTUR AKIBAT PERUBAHAN BEA MASUK IMPOR 2020 DAN PANDEMI COVID-19 - Antyo Pracoyo; Billy Fadhilla Maliki; Ferdy Adi Sampurno; Galih Sejati (Media Ekonomi, 2021)
Investment is a commitment to sacrifice current consumption with the aim of increasing consumption in the future. On January 30, 2020, the Ministry of Finance issued Regulation of the Minister of Finance number PMK199/PMK.10/2019, concerning import duty tariffs for retail imported goods. This regulation aims to protect the domestic industry due to the increasing transaction of imported goods using online methods, and is expected to reduce the current balance deficit. This research uses event studies method, which is when the new policy will affect the share price of certain sectors. However, when the provision is established it only has a relatively less strong influence on the volatility of its main share price in the manufacturing sector. Stock price volatility in IDX occurs precisely when the world occurs covid-19 pandemic and the announcement of events that in Indonesia is also affected starting in March 2020. The share price in the manufacturing sector has dropped sharply but there are also subsectors that have strengthened in price